IMPLEMENTASI PROGRAM PERPUSTAKAAN KELILING OLEH DINAS PERPUSTAKAAN DAN KEARSIPAN UNTUK MENINGKATKAN MINAT BACA PELAJAR KABUPATEN TANAH DATAR TAHUN 2022 - Safaraz, Daffa Surya; Hadi, Sofyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Mobile libraries are an innovative solution to increase access to literacy in areas that lack library facilities. This initiative involves the use of modified vehicles to carry various types of books and other reading materials to remote communities. The main aim of a mobile library is to provide easy access to reading materials, increase interest in reading, and support informal education in the community. These programs are usually run by local governments, non-governmental organizations, or local communities, and often involve additional activities such as shared reading sessions, literacy workshops, and storytelling competitions. The purpose of this research is to find out the implementation carried out by the Tanah Datar Regency Library and Archives Service in increasing the reading interest of Tanah Datar Regency Students by referring to the theory of program implementation according to Jones (1996:295): 1. The objectives of the activities to be achieved. 2. Activities taken to achieve goals. 3. Rules that must be adhered to and procedures that must be followed. 4. Estimated budget required. 5. Implementation strategy.. This research is descriptive qualitative research with the main data sources being primary data and secondary data. The data collection techniques used were interview and documentation techniques. This data analysis technique is Data Reduction, Data Presentation and Conclusion Drawing. The results of this research are that the programs carried out by the Tanah Datar Regency government and the Tanah Datar Library and Archives Service are not yet optimal due to a lack of funds and infrastructure. Key Words : Program Objectives, Program Activities, Program Related Rules